2010
DOI: 10.1227/01.neu.0000371988.73620.4c
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Results in Local Glutamate and Adenosine Release

Abstract: Objective-Several neurologic disorders are treated with deep brain stimulation; however, the mechanism underlying its ability to abolish oscillatory phenomena associated with diseases as diverse as Parkinson's and epilepsy remain largely unknown. In this study we sought to investigate the role of specific neurotransmitters in deep brain stimulation (DBS) and determine the role of non-neuronal cells in its mechanism of action.Methods-We used the ferret thalamic slice preparation in vitro, which exhibits spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 60 publications
5
110
1
1
Order By: Relevance
“…Cunha et al [39] reported that levels of adenosine in hippocampal slices were increased by high-frequency, but not low-frequency stimulation, and recently, the involvement of adenosine in the therapeutic mechanism of thalamic DBS has been suggested [40,41] . The marked suppression and slow recovery of both spontaneous and ictal activity following high-frequency DBS bursts are consistent with this type of metabotropic regulatory mechanism; however, direct evidence is not provided by our results.…”
Section: Discussionmentioning
confidence: 99%
“…Cunha et al [39] reported that levels of adenosine in hippocampal slices were increased by high-frequency, but not low-frequency stimulation, and recently, the involvement of adenosine in the therapeutic mechanism of thalamic DBS has been suggested [40,41] . The marked suppression and slow recovery of both spontaneous and ictal activity following high-frequency DBS bursts are consistent with this type of metabotropic regulatory mechanism; however, direct evidence is not provided by our results.…”
Section: Discussionmentioning
confidence: 99%
“…This is important in light of recent evidence suggesting that PFC glia might be involved in mechanisms of depressivelike behavior and antidepressant treatments in rats (65,66). Furthermore, adenosine and glutamate released by glial cells have been shown to contribute to the mechanisms of thalamic DBS in vitro (67). At present, there is still no conclusive evidence supporting a role for glia in the antidepressant-like effects of vmPFC DBS.…”
Section: Mechanisms Involved In the Effects Of Vmpfc Stimulation In Tmentioning
confidence: 94%
“…The electrical current also acts on synapses and triggers adjacent astrocytes to release a wave of calcium and to promote local release of neurotransmitters (e.g. adenosine and glutamate) from excitatory efferent neurons [8,9,10]. In addition, this intervention produces global increases in cerebral blood flow [11] and stimulates neurogenesis [12].…”
Section: Mechanisms Of Dbsmentioning
confidence: 99%